ECCLESIASTICAL LEGISLATIONS FOR THE PROTECTION OF MINORS AND VULNERABLE PERSONS AGAINST SEXUAL ABUSE AND THEIR IMPLEMENTATION IN INDIAN CHURCH: DEVELOPMENTS AND LIMITATIONS - Lavy, Shiju K. (Asian Horizons, 2020)
Sexual violence against minors is a heinous crime against humanity. The Indian Church along with Universal Church declares zero tolerance to this evil as graviora delicta. Measures to handle such cases sometimes become a failure because of ineffective implementation of the legislation. In this context, the article discusses the developments of ecclesiastical legislations for protection of minors and vulnerable adults and their limitations. The article is divided into five parts: The first part is a terminological explanations of Sexual Abuse of Minors in India; the second part explains the major Ecclesiastical Legislation by the Universal Church; the third part expounds the promulgations of the Indian Church in this regard; the fourth part discusses the limitations and failures of the Indian Church in implementing the guidelines and legislations of the universal and local ecclesiastical bodies; and the last part proposes a few recommendations for effective protection of minors and vulnerable persons in the Indian Church.